2018
DOI: 10.1111/epi.14583
|View full text |Cite
|
Sign up to set email alerts
|

Subcentimeter epilepsy surgery targets by resting state functional magnetic resonance imaging can improve outcomes in hypothalamic hamartoma

Abstract: Objective: The purpose of this study is to investigate the outcomes of epilepsy surgery targeting the subcentimeter-sized resting state functional magnetic resonance imaging (rs-fMRI) epileptogenic onset zone (EZ) in hypothalamic hamartoma (HH). Methods: Fifty-one children with HH-related intractable epilepsy received anatomical MRI-guided stereotactic laser ablation (SLA) procedures. Fifteen of these children were control subjects (CS) not guided by rs-fMRI. Thirty-six had been preoperatively guided by rs-fMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 55 publications
4
57
0
2
Order By: Relevance
“…Those patients with a hypothalamic hamartoma received a secondary analysis described in detail in Boerwinkle et al The ICA results were used to filter out noise, and a seed analysis (searchlight analysis [V.L.B.]) within the hamartoma was performed both before and after surgery . The preoperative rs‐fMRI was registered to the postoperative image anatomical MRI for visual inspection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Those patients with a hypothalamic hamartoma received a secondary analysis described in detail in Boerwinkle et al The ICA results were used to filter out noise, and a seed analysis (searchlight analysis [V.L.B.]) within the hamartoma was performed both before and after surgery . The preoperative rs‐fMRI was registered to the postoperative image anatomical MRI for visual inspection.…”
Section: Methodsmentioning
confidence: 99%
“…Those patients with a hypothalamic hamartoma received a secondary analysis described in detail in Boerwinkle et al 29 The ICA results were used to filter out noise, and a seed analysis (searchlight analysis [V.L.B.]) And, barring anatomical differences created from surgery, residual detected spatial pattern matching expected RSNs for spatial location.…”
Section: Independent Component Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the electrodes designed for disconnecting the attachment of the HHs are located near the interface. Due to the small sample size, we have not been able to determine the subcentimeter targets for ablation like that in fMRI ( 37 ). There was no difference of epileptic activity between the electrodes near the interface and those in deeper area.…”
Section: Discussionmentioning
confidence: 99%
“…Boerwinkle et al 1 have recently suggested that using rs-fMRI might improve outcomes using MRI-guided stereotactic laser ablation for hypothalamic hamartomas. We have demonstrated before how stereotactic radiosurgical thalamotomy for drug-resistant essential tremor (ET) correlates with changes within large-scale brain networks ( Figure 1) [6][7][8][9][10] .…”
Section: Dear Editormentioning
confidence: 99%